Oviposition of Spodoptera exigua on Shallot in Monoculture and Polyculture System with Groundnuts and Cowpeas - Widotami, Diarsi Atiki; Witjaksono, Witjaksono; Putra, Nugroho Susetya (Universitas Gadjah Mada, 2025)
Spodoptera exigua is the main pest of shallot (Allium cepa) that cause significant damage on leaves and reduce yield. Polyculture is a potential management strategy against S. exigua by deterring their oviposition behavior. This study aims to evaluate S. exigua oviposition preference on shallots grown in monoculture or polyculture system. In the no-choice assay, shallots, groundnuts (Arachis hypogaea), and cowpeas (Vigna unguiculata) were planted alone while shallots were planted with either groundnuts or cowpeas plant in the choice assays. Observed parameters were the number of eggs laid by female S. exigua on shallot plants on each day and the total after the oviposition periods. Results showed that the number of eggs laid on shallots were significantly lower in polyculture systems (161.67 ± 96.02) compared to ones planted in monoculture systems(309.67 ± 39.70). This implies that polyculture systems between shallots with groundnuts or cowpeas can potentially reduce S. exigua oviposition on shallots.